The boot and shoe industry of Saorstat Eireann - McCarthy, C.P. (Statistical and Social Inquiry Society of Ireland, 1935)
The Irish market in footwear was always of great importance to the British importers. When the tariff was first imposed in 1924 "the Irish Free State took one-third of the total British exports of footwear." (Economic Journal, Vol. 37, June, 1927.) When introducing the first tariff the Minister for Finance "designated it as a limited experiment in the use of a tariff with the object of stimulating the industry of the Soarstat." (Economic Journal, loc. cit.) In this paper I propose to examine the results of that "limited experiment" which has now developed into the more full blooded experiment of Quota prohibition.
To be read on Thursday, 28th March, 1935
Keywords: Footware industry; Tariff; Quotas; 314.15